Pengaruh Pemberian MSG Terhadap Pertumbuhan dan Hasil Selada Keriting (Lactuca sativa L.) - vivi alayda fatikasari; Anis Sholihah; Siti Muslikah (AGRONISMA, 2022)
The use of monosodium glutamate (MSG) can increase the productivity of curly lettuce (Lactuca sativa L). The purpose of this study was to determine the effect of MSG on the growth and yield of lettuce on soil mixed with compost. used is a Simple Randomized Design with MSG dose treatment of 5 levels, namely P0 Design: 0 g/plant, P1: 5 g/plant, P2; 10 g/plant, P3: 15 g/plant and P4; 20 g/plant. The results showed that there was an effect of MSG dosage on growth parameters where the best P0 (MSG dose 0 g) and P3 (MSG dose 15 g) obtained plant heights P0 (19.50 cm) and P1 (19.83 cm) at 35 after planting, the number of leaves P3 (8.00 pieces) at 35 after planting, leaf area P0 (121.12 cm2) and P1 (126.95 cm2) at after planting. In the yield parameters, the highest total plant fresh weight was obtained, namely the P3 treatment (68.08 g).Keywords : monosodium glutamate, lettuce, vegetative growth